DETERMINATION OF GOLD, SILVER AND PLATINUM-GROUP ELEMENTS IN GEOCHEMICAL REFERENCE MATERIALS BY DIRECT ATOMIC EMISSION SPECTRAL ANALYSIS USING A MULTICHANNEL ANALYSER RECORDING DEVICE - Zayakina S.B.; Anoshin G.N. (My University, 2001)
A procedure for the analysis of geochemical samples has been developed based on direct atomic-emission spectrometry for the determination of silver, gold and the platinum-group elements. Instrumentation comprised a DC arc emission two-jet plasmatron coupled to a diffraction spectrograph and multichannel analyser for recording emission spectra. Spectrum analysis used a comprehensive library of spectral lines for practically all elements excited using this emission source. The software programme for the automatic registration of spectra and subsequent data processing are described and results presented for a number of geochemical reference materials.